Prognostic Value of Serum Galectin-3 in Chronic Heart Failure: A Meta-Analysis - Cheng, Zhendong; Cai, Kefeng; Xu, Chaoxian; Zhan, Qiong; Xu, Xingbo; Xu, Dingli; Zeng, Qingchun (Frontiers in Cardiovascular Medicine, 2022)
Objective:In this meta-analysis, we sought to evaluate the association between serum galectin-3 and all-cause death (ACD) and cardiovascular death (CVD) in chronic heart failure (CHF) patients Methods:The PubMed and Embase databases were searched for studies with data on serum galectin-3 and ACD and CVD in CHF patients. The hazard ratios (HRs) of ACD and CVD were calculated and presented with 95% CIs.HRs were pooled using fixed effects or random effects models when appropriate.Sensitivity analysis,subgroup analysis and meta-regression were applied to explore the origin of heterogeneity.Publication bias was assessed by visual inspection of Begg’s funnel plot,and the possibility of publication bias was assessed by Egger’s test. Results:A total of 6440 patients from 12 studies were finally enrolled in the meta-analysis.The summary results showed that higher serum galectin-3 was independently associated with a higher risk of ACD (HR, 1.38; 95% CI, 1.14 to 1.67) and CVD (HR, 1.13; 95% CI, 1.02 to 1.25)in CHF patients. In the subgroup analyses, higher serum galectin-3 was associated with an increased risk of all-cause death in all subgroups.The pooled HR of the shorter follow-up group (1.78; 95% CI, 1.50–2.11) was higher than the pooled HR of the longer follow-up group (1.15; 95% CI, 1.05–1.25). A sensitivity analysis of omitting one study in each turn showed that Koukoui et al.’s study had the largest influence on the risk of all-cause death: the pooled HR without this study was 1.24 (95% CI, 1.09–1.40). All-cause death publication bias was not detected(Pr>|z|=0.35 for Begg’s test and P>|t|=0.15 for Egger’s test). Conclusions: Galectin-3 may be a predictor of both all-cause and CV death in CHF outpatients. The present meta-analysis supports the use of galectin-3 for risk stratification in patients with CHF.